Influence of substrate temperature and post-annealing treatment on the microstructure and electric properties of ZnO:Al thin films deposited by sputtering - Garcia, Cibeli Navarro Belletti (2013)
In this work, it is reported the characterization of the microstructure and electric properties of ZnO:Al thin films produced by magnetron sputtering. An AZOY sputtering target (98 wt% ZnO + 2 wt% Al2O3) was used as source material. The microstructure, optical and electrical properties of ZnO:Al thin films were investigated and correlated with substrate deposition temperature and post-annealing temperature. It is demonstrated that the microstructural, electrical and optical properties of the as-deposited thin films are dependent on the substrate temperature. The crystalline texture of ZnO:Al was improved with temperature deposition as shown in the EBSD analysis and X-ray diffraction. ZnO:Al thin film deposited at 250 ºC exhibited very good electrical conductivity, as high as 200 S.cm-1 with an activation energy of 5.4 meV. As substrate temperature or heat treatment temperature is increased there is an apparent blue-shift on the absorption edge of the transmittance spectra, which can be explained by the Burnstein-Moss effect.